2003
DOI: 10.1242/jeb.00054
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic plasticity and critical temperatures for aerobic scope in a eurythermal marine invertebrate (Littorina saxatilis, Gastropoda: Littorinidae) from different latitudes

Abstract: SUMMARYEffects of latitudinal cold adaptation and cold acclimation on metabolic rates and aerobic scope were studied in the eurythermal marine gastropod Littorina saxatilis from temperate North Sea and sub-arctic White Sea areas. Animals were acclimated for 6-8 weeks at control temperature (13°C) or at 4°C, and their respiration rates were measured during acute temperature change (1-1.5°C h-1) in a range between 0°C and 32°C. In parallel, the accumulation of anaerobic end products and changes in energy status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(118 citation statements)
references
References 45 publications
(53 reference statements)
4
112
1
1
Order By: Relevance
“…As the interdependence of thermal tolerance and aerobic scope have only recently been discussed as a unifying principle among animals (Pörtner, 2001) these relationships have not been systematically investigated. However, invertebrate examples from the intertidal zone where they may be exposed to midday sunshine and heat, would most adequately illustrate that extreme heat goes hand in hand with anaerobic metabolism and passive survival (Sokolova and Pörtner, 2003) and thus very likely involves a metabolic depression scenario which contributes to energy savings and thereby extends the period during which heat beyond the critical temperature can be tolerated.…”
Section: Temperature Induced Hypoxic Hypometabolism?mentioning
confidence: 99%
See 1 more Smart Citation
“…As the interdependence of thermal tolerance and aerobic scope have only recently been discussed as a unifying principle among animals (Pörtner, 2001) these relationships have not been systematically investigated. However, invertebrate examples from the intertidal zone where they may be exposed to midday sunshine and heat, would most adequately illustrate that extreme heat goes hand in hand with anaerobic metabolism and passive survival (Sokolova and Pörtner, 2003) and thus very likely involves a metabolic depression scenario which contributes to energy savings and thereby extends the period during which heat beyond the critical temperature can be tolerated.…”
Section: Temperature Induced Hypoxic Hypometabolism?mentioning
confidence: 99%
“…Early evidence collected in marine invertebrates (annelids and sipunculids) demonstrated a transition to anaerobic metabolism (including mitochondrial anaerobiosis) at both cold and warm temperature extremes (Zielinski and Pörtner, 1996;Sommer et al, 1997), later on confirmed in crustaceans (Frederich and Pörtner, 2000) and molluscs, i.e. bivalves, gastropods and cephalopods (Pörtner and Zielinski, 1998;Pörtner et al, 1999;Peck et al, 2002;Sokolova and Pörtner, 2003). Studies in a sipunculid (Sipunculus nudus, Zielinski and Pörtner, 1996) and the spider crab (Maja squinado, Frederich and Pörtner, 2000) investigated the pattern of coelomic fluid/haemolymph oxygen tensions in relation to warming and/or cooling and demonstrated development of hypoxia which preceded the onset of anaerobic metabolism towards both cold and warm temperature extremes.…”
Section: Introduction: a Role For Hypoxia In Thermal Limitation?mentioning
confidence: 98%
“…The concept has since been applied to a great range of aquatic and terrestrial species (e.g. Auer et al 2015;Bishop 1999;Moberly 1968;Overgaard et al 2012;Schippers et al 2014;Sokolova and Pörtner 2003). On the surface, aerobic scope seems to be a relatively straightforward variable.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, metabolic networks involve series of interconnected chemical reactions catalyzed by enzymes, allowing the transformation of input substrates into intermediate or final metabolites. These networks play an essential role in an organism's growth, reproduction, and ability to maintain cell integrity and to respond to environmental changes (1,2). The metabolic fluxes, as well as the metabolite concentrations, are governed by the activity of the enzymes, which depends on three types of factors: kinetic parameters, enzyme abundance, and activation state of the enzyme.…”
mentioning
confidence: 99%